The energy strategy of Turkey - A. Yu. Konovalova (Вестник университета)
The article is devoted to the energy strategy of Turkey, which is not fixed in legislation, but its particular elements are presented in various national strategies, development plans and programs. The author aims to identify the strengths and weaknesses of the country’s energy policy, as well as opportunities and risks using SWOT analysis. In the article, the author highlights the main elements and directions of Turkey’s energy strategy and notes that many mentioned tasks have already been achieved, that indicates a high level of the energy policy implementation. However, author believes that after 2023, when updating strategic plans, numerical indicators will undergo changes, and the general vectors of the Turkish energy sector development will remain unchanged. In addition, the article presents a general state analysis of Turkish energy sector, the main energy resources, suppliers and infrastructure.